Effects of acteoside from Cistanche tubulosa on the plasma metabolome of cancer-related fatigue mice inoculated with colon cancer cells - Zhang, Shilei; Gong, Fukai; Liu, Jiali; You, Shuping; Liu, Tao; Yang, Jianhua; Hu, Junping (Frontiers in Pharmacology, 2025)
ObjectiveTo elucidate the metabolic mechanisms by which acteoside (ACT) isolated from Cistanche tubulosa alleviates cancer-related fatigue (CRF) in a murine model of colon cancer with cachexia.MethodsBALB/c mice inoculated with C26 colon cancer cells were treated with paclitaxel (PTX, 10 mg/kg) and ACT (100 mg/kg) alone or in combination for 21 days. Fatigue-associated behaviors, tumor inhibition rate, and skeletal muscle morphology assessed by hematoxylin-eosin (H&E) staining and electron microscopy were evaluated. Finally, liquid chromatography-mass spectrometry (LC/MS) was employed to investigate alterations in the plasma metabolic profile of tumor-bearing mice with CRF in response to ACT treatment, and the affinity between metabolite-associated proteins and ACT was verified by Surface plasmon resonance (SPR) assay.ResultsOur study demonstrated the presence of CRF in the colon cancer mouse model, with the severity of fatigue increasing alongside tumor growth. Administration of ACT ameliorated both tumor burden and PTX-induced muscle fatigue-like behavior. LC/MS analysis identified a panel of differentially regulated metabolites, including trans-aconitine, citric acid, 3-coumaric acid, ephedrine, thymine, cytosine, indole-3-acetic acid, and pantothenol-9. These metabolites were primarily enriched in pathways associated with valine biosynthesis, tyrosine metabolism, tryptophan metabolism, and biosynthesis of pyridine alkaloids. Furthermore, several key enzymes, including CYP3A4, CYP19A1, CYP2E1, TNF, BCL-2, RYR2, and ATP2A1, were identified as potential targets underlying the anti-CRF effects of ACT.ConclusionThis study suggests that ACT derived from C. tubulosa harbors protective properties against cancer-related fatigue mediated by tumor cells.